Implementasi Pelibatan Masyarakat dalam Meningkatkan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 di MIN 1 Bandung - Anisa, Ana; Nugraha, Mulyawan Safwandy (Lembaga Yasin AlSys, 2024)
Indonesia's education policy is closely linked to other public policies and can change if public policies change. Education requires community participation to produce an effective learning community. This research uses a qualitative approach with descriptive method located in MIN 1 Bandung. With the committee, some programs run smoothly, and socialization with students can be coordinated easily. The participation of the committee and other elements such as Polsek, Puskesmas, and local RT/RW received positive responses, especially with programs that involve interaction with the surrounding environment and habituation programs that create new habits in the school environment. Community participation or individual participation in the development of self, life, and the environment, which involves two-way interaction between the government and the community.